Marsupials don't adjust their thermal energetics for life in an alpine environment. - Cooper, Christine; Withers, Philip; Hardie, A.; Geiser, F. (Taylor & Francis Group, 2016)
Marsupials have relatively low body temperatures and metabolic rates, and are therefore considered to be maladapted for life in cold habitats such as alpine environments. We compared body temperature, energetics and water loss as a function of ambient temperature for 4 Antechinus species, 2 from alpine habitats and 2 from low altitude habitats. Our results show that body temperature, metabolic rate, evaporative water loss, thermal conductance and relative water economy are markedly influenced by ambient temperature for each species, as expected for endothermic mammals. However, despite some species and individual differences, habitat (alpine vs non-alpine) does not affect any of these physiological variables, which are consistent with those for other marsupials. Our study suggests that at least under the environmental conditions experienced on the Australian continent, life in an alpine habitat does not require major physiological adjustments by small marsupials and that they are physiologically equipped to deal with sub-zero temperatures and winter snow cover.